Komodifikasi Konten di Radio Berita Lokal: (Studi Kasus Intrinsik Radio PRFM 107.5 News Channel Bandung) - Nadya Yasmine Khaerunnisa; Achmad Abdul Basith; Rinda Aunillah Sirait (Institut Nalanda, 2026)
Radio PRFM 107.5 News Channel Bandung has established its reputation as a citizen journalismbased local news radio through the slogan